2018
DOI: 10.1007/s00429-018-1677-2
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical predictors of cognitive decline after subthalamic stimulation in Parkinson’s disease

Abstract: We investigated whether pre-operative MRI measures of focal brain atrophy could predict cognitive decline occurring after deep brain stimulation (DBS) of the subthalamic nucleus (STN) in patients with Parkinson's disease (PD). For that purpose, we prospectively collected data of 42 consecutive patients with PD who underwent bilateral STN-DBS. Normalized brain structure volumes and cortical thicknesses were measured on pre-operative T1-weighted MRI. Patients were tested for their cognitive performances before s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
(68 reference statements)
0
12
0
Order By: Relevance
“… 8.8 ± 2.0 mo Med off: 39.2 ± 19.1 NR Blume; 2017 29 40 (30/10) BL STN 12.5 ± 4.5 61.8 ± 6.7 ↑ WML & Rapid onset of dementia within 1 yr. ↑ WML & Increased rate of decline in cognitive composite score within 3 yr. 3 yr Med off: 33.6 ± 10.7; Med on:12.2 ± 6.6 Med NR: PDpD after 3 yr:34.8 ± 11.3 NC or MCI after 3 yr:30.2 ± 7.8 Puy; 2018 31 Case study (1, female) STN 7 68 A medial temporal lobe atrophy score of 2 of the patient who developed dementia after deep brain stimulation. / Med off:30 / Planche; 2018 15 42 (26/16) BL STN 10 [6–17] 64 [45–70] ↓ The left nucleus accumbens & The variation of the initiation/perseveration subscore of the MDRS. ↑ The left lateral ventricle & The variation of the total MDRS score/ the initiation/perseveration subscore.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 8.8 ± 2.0 mo Med off: 39.2 ± 19.1 NR Blume; 2017 29 40 (30/10) BL STN 12.5 ± 4.5 61.8 ± 6.7 ↑ WML & Rapid onset of dementia within 1 yr. ↑ WML & Increased rate of decline in cognitive composite score within 3 yr. 3 yr Med off: 33.6 ± 10.7; Med on:12.2 ± 6.6 Med NR: PDpD after 3 yr:34.8 ± 11.3 NC or MCI after 3 yr:30.2 ± 7.8 Puy; 2018 31 Case study (1, female) STN 7 68 A medial temporal lobe atrophy score of 2 of the patient who developed dementia after deep brain stimulation. / Med off:30 / Planche; 2018 15 42 (26/16) BL STN 10 [6–17] 64 [45–70] ↓ The left nucleus accumbens & The variation of the initiation/perseveration subscore of the MDRS. ↑ The left lateral ventricle & The variation of the total MDRS score/ the initiation/perseveration subscore.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies that were included in our review reported associations of brain volumetry with the cognitive outcome 15 , 22 , 28 33 . ROI analysis assessing specific structures was adopted in these studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent autopsy study on 25 postmortem brains of PD-MCI patients by Knox and colleagues, however, found a broad variety of pathological changes including α-synuclein and cholinergic pathology as well as cerebral amyloid angiopathy [26]. Therefore, it could be interesting to look further into other pathologies like white matter lesions and their underlying risk factors and into the size and integrity of other non-cholinergic structures discussed to play a role in cognition in PD like the nucleus accumbens [27] and the pulvinar [28].…”
Section: Discussionmentioning
confidence: 99%